2017
DOI: 10.18632/oncotarget.20346
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of PD-L1 expression on circulating epithelial tumor cells (CETCs) could be a potential biomarker to select patients for treatment with PD-1/PD-L1 inhibitors in early and metastatic solid tumors

Abstract: BackgroundThe current cancer research strongly focuses on immune therapies, where the PD-1, with its ligands plays an important role. It is known that PD-L1 is frequently up-regulated in a number of different cancers and the relevance of this pathway has been extensively studied and therapeutic approaches targeting PD-1 and PD-L1 have been developed. We used a non-invasive, real-time biopsy for determining PD-L1 and PD-L2 expression in CETCs of solid cancer patients.MethodsCETCs were determined from blood of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 45 publications
5
65
0
Order By: Relevance
“…Potential clinical uses of blood-based CTC and ctDNA that are not offered by tumor tissue sequencing include monitoring the persistence of radiologically undetectable tumors (e.g., minimal or molecular residual disease), prediction of recurrence (e.g., persistent CTC associated with risk of relapse in breast cancer) [60], monitoring of treatment response (e.g., CTC dynamics in prostate and breast cancer patients treated with chemotherapy) [61,62], early detection of resistance mechanisms [63,64], assessment of tumor burden (e.g., correlation between tumor burden and ctDNA variant allele frequency in NSCLC) [65], tracking the clonal evolution of tumors [66], and dynamic evaluation of immune biomarkers such as PD-L1 expression and tumor mutation burden [67][68][69].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Potential clinical uses of blood-based CTC and ctDNA that are not offered by tumor tissue sequencing include monitoring the persistence of radiologically undetectable tumors (e.g., minimal or molecular residual disease), prediction of recurrence (e.g., persistent CTC associated with risk of relapse in breast cancer) [60], monitoring of treatment response (e.g., CTC dynamics in prostate and breast cancer patients treated with chemotherapy) [61,62], early detection of resistance mechanisms [63,64], assessment of tumor burden (e.g., correlation between tumor burden and ctDNA variant allele frequency in NSCLC) [65], tracking the clonal evolution of tumors [66], and dynamic evaluation of immune biomarkers such as PD-L1 expression and tumor mutation burden [67][68][69].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…The evaluation of PD-L1 expression on CTCs has been assessed in different solid tumors including lung [66,[78][79][80][81][82][83][84], bladder [85], breast [86], HNSCC [87,88], colon [84,89] and prostatic carcinoma [84,89] (Table 2). Independently of the technical issues cited above, other challenges rapidly emerged: (i) is PD-L1 expressed on all CTCs or only in a subpopulation of CTCs?…”
Section: Analysis Of the Expression Of Pd-l1 In Ctcsmentioning
confidence: 99%
“…The first study on expression of PD-L1 on CTCs was reported in patients with metastatic breast carcinoma (Mazel et al, 2015), and later it was investigated in other types of cancer. Further study on CTC/PD-L1 indicated that the frequency of PD-L1 positive CTCs are significantly higher in metastatic breast cancer patients compared to non-metastatic patients (Schott et al, 2017). These findings suggested CTC/PD-L1 assay as a potential non-invasive marker for stratification of patients benefiting from anti-PD-L1 therapies in clinical trials (Mazel et al, 2015;Schott et al, 2017).…”
Section: Liquid Biopsies Biomarkersmentioning
confidence: 92%
“…Further study on CTC/PD-L1 indicated that the frequency of PD-L1 positive CTCs are significantly higher in metastatic breast cancer patients compared to non-metastatic patients (Schott et al, 2017). These findings suggested CTC/PD-L1 assay as a potential non-invasive marker for stratification of patients benefiting from anti-PD-L1 therapies in clinical trials (Mazel et al, 2015;Schott et al, 2017). The expression of another important immune checkpoint member, B7-H3, on CTCs of breast cancer patients has been also reported.…”
Section: Liquid Biopsies Biomarkersmentioning
confidence: 96%